ANALISIS KUALITAS PELAYANAN TRANSPORTASI ONLINE DI MASA PANDEMI COVID-19 MENGGUNAKAN INTEGRASI METODE IPA DAN KANO - Anselmus Aprilio Mengi; Desrina Yusi Irawati (Universitas PGRI Madiun, 2022)
Covid-19 affects many people's economic activities, one of which is online transportation services. Online transportation service providers must implement health protocols on their services in accordance with government regulations. The purpose of this study was to measure customer satisfaction with the quality of online transportation services in Surabaya during the Covid-19 period. Measurements were carried out by integrating the IPA-Kano method. The results of this measurement are expected to be input for online transportation companies in improving the quality of online transportation services during the Covid-19 period. Based on the IPA analysis, the results of the calculation of the average total value of performance are 3.96 and the average total value of expectations is 4.48. The average total value of performance is smaller than the average total value of expectations. This shows that the performance of online transportation services is still lower than customer expectations. The results of the IPA-Kano integration analysis show that there are 14 attributes that must be maintained and 12 attributes that need to be improved. The priority attributes that need to be improved are drivers providing health protocol tools such as masks and handsanitizers, and drivers having broad insight about the road to be taken.